Capability of Cellulolytic Degradation (BSD) Bacteria (CDB) to Remodel Organic Waste into Compost - Eri Samah Samah; Misdawati (Jurnal Pertanian Tropik, 2019)
Capability of Cellulolytic Degradation (BSD) Bacteria (CDB) to Remodel Organic Waste intoCompost The purpose of this study was to obtain superior cellulolytic bacteria from acid soils as astarter for the degradation of organic waste in the city of Padang by testing the activity of cellulaseenzymes. The method used in the factorial method is the Cellulolytic Degradation Bacteria factorwith the Organic Waste of Padang City. This research was conducted at the Plant PhysiologyLaboratory and the Soil Science Laboratory, Faculty of Agriculture. The research activity was begunby isolating the bacteria from acid soil, followed by testing the enzyme activity of the specific mediumof carboxyl methylcellulose (CMC) medium. Factorial Complete Random Design Method. The firstfactor was selected 3 isolates of cellulolytic bacteria, the second-factor main market organic wasteat of Padang and was two treatments namely unstable sterile (A) and nonsterile (B). The researchresults obtained 6 isolates of cellulolytic bacteria with a clear zone index ≥ 2, namely Km25,Sr. 75, Jm, U-6, G-8, and Km 13, respectively 3.12; 3.04; 3.0; 2.04; 2.00, and 2.04, and used forcomposting organic waste 3 isolates of clear zone bacteria ≥ 3.0 isolates of KM25, Sr75, and JMrespectively 3.12; 3.04; 3.01. Non-sterile organic waste is better than sterile due to the non-sterile,there is the help of battery change from the trash. Conclusion The best composting material is notsterilized, and better bacteria decompose the waste combined with the three isolates KM25, SR75,and JM.